Students’ Thinking Process in Solving Abstraction Problems in Mathematics: A Case Study on Limited Test of Development Research Instrument - Ade Andriani, Izwita Dewi, Nurhasanah Siregar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Abstraction is an activity performed in daily life and the ability needs to be developed, especially in mathematics learning. The information on how students solve problems is important for teachers to consider the strategies to use in helping the students. This research was carried out due to the answers’ variations discovered in abstraction problems. Therefore, it aimed to investigate students' thinking processes in solving problems. The research was a combination of the Sequential Explanatory Design model that used both quantitative and qualitative data collection and analysis methods, while the subjects used were 33 students of seventh grade. The result showed guessing and drawing was used to solve the abstraction problems, but only one student employed patterns and pictures in the process. Consequently, training students on critical thinking skills utilization to solve abstraction problems easily was suggested in mathematics learning.